P169 Health utilities index-3 outcomes of injuries occurring to youth living on agricultural operations in the midwest united states: regional rural injury study – iii. (1st September 2016) - Gerberich, Susan; Ryan, Andrew; Alexander, Bruce; Renier, Colleen
Abstract : Background: Few studies have examined the impact of childhood injuries on health-related quality of life. The Health Utilities Index Mark 3 (HUI3) provides an opportunity for such investigation. Objectives: Analyse associations between injuries incurred by youth on agricultural operations and short- and long-term changes in HUI3 scores. Methods: A random sample of 6, 400 operations was selected from each Midwest state (Minnesota, Wisconsin, North Dakota, South Dakota, and Nebraska), using the US Department of Agriculture, National Agricultural Statistics Service's Master ListFrame. Using computer-assisted telephone interviews, operations were screened for eligibility: agricultural households with youth (<20 years of age); actively farming/ranching as of January 1, 2007. Baseline data were collected from 1, 459 eligible agricultural operations. Two six-month injury data collection periods followed baseline collection; annual follow-up evaluation data were collected for two years. Case households included injured youth while control households with no injured youth, were randomly selected at a 3:1 ratio. Analyses included all youth 5–19 years, with valid HUI3 multi-attribute utility scores. Linear mixed models were used to analyse for changes in HUI3 scores between baseline and follow-up periods between injured and non-injured youth, adjusted for within-household, within-person correlation, and non-response. Results/Outcomes: Between baseline and six-month follow-up, injured youth, compared with non-injured youth, were associated with significant differences in overall HUI score changes (−0.049; 95% C.I. −0.070, −0.028) and the pain component of HUI3 (−0.070; −0.094, −0.046). When examining youth with severe injuries (>7 days restricted activity), the short-term differences in overall HUI3 were even more pronounced (−0.079; −0.109, −0.049). No differences in HUI3 were found at one- and two-year follow up periods. Conclusions: Injuries to these youth resulted in significant reductions in short-term HUI3 health status scores, reflecting increased disability and suggesting opportunities for intervention.